Foresight: A breath of fresh air on the East River. The expansion of the UN Security Council triggers unexpected reforms - Judith Vorrath; Lars Brozus (Stiftung Wissenschaft und Politik (SWP), 2024)
Surprise and jubilation in the United Nation Security Council (UNSC): 2028 begins with a bang. The permanent members of the body declare that they will voluntarily renounce their right of veto in cases of mass atrocities. This self-limitation, achieved after a long struggle, would have been unthinkable without the far-reaching reform of the Security Council that preceded it. The initiative, based on an earlier Franco-Mexican proposal and the Code of Conduct of the Accountability, Coherence and Transparency Group (ACT Group), came from the new members of the enlarged UNSC. Since 2027, it has consisted of 27 instead of 15 members. Germany is among the new members. In her first speech after the enlargement, the German Ambassador to the UN noted with a wink that her country had hoped to be represented in 2027/28 even without the reform. After all, Berlin had already announced in 2023 that it would stand for election as a non-permanent member in 2027/28. However, it was not foreseeable at the time that Germany would now be one of the six new semi-permanent members of the Security Council.
Keywords: 320; UN Security Council (UNSC); UN reform; UN Charter; New 6 (N6); Germany; Japan; Brazil; India; South Africa and Nigeria; UN General Assembly (UNGA); Accountability; Coherence and Transparency Group (ACT Group); permanent five (P5); Ezulwini Consensus; Responsibility to Protect (R2P); China; Russia; France; Germany; Africa